The Radiantguard umbrella (blueprint) / Farah Aisyah Abdul Kadir … [et al.]. - Abdul Kadir, Farah Aisyah; Zulkefli, Zulfa Alwiyah; Abdullah Hedhir, Nur Ain; Mohd Ariff, Nur Shamimi Ayuni; Abd Razak, Nur Elya Natasha; Izzanol Bokiah, Ammar Faid (2024)
Brief Description of The Business and Product Concepts: GOLDEN TECH is a growing company in technology and innovation, this company exists because of the problem that people experience that no one could solve, creating and innovating an existing product into a newer and better one is GOLDEN TECH expertise. GOLDEN TECH comes out with a new version of umbrella called “The Radiantguard Umbrella”. Definitely not a regular umbrella that can be found in the convenience store. We added some extra features to be more convenient to the users. This umbrella is made up of Water-Repellent Coating. Our umbrellas come with special coatings that make them resistant to water. This coating helps rainwater bead up and roll off the surface of the umbrella rather than being absorbed. We also added a glow in the dark feature to our umbrella, the glowing feature makes you more visible to others during nighttime or in a situation with reduced lighting, enhancing when walking. The Target Market and Projections: Our multifunction umbrella is crafted to cater to the diverse needs of everyone, offering a blend of practicality and style that resonates with individuals of all ages and backgrounds who appreciate the convenience of a versatile and reliable accessory.